Effects of Multimedia Advertisement Features on Customer Satisfaction in Kenyan 5-Star Hotels - Kiprop, Carolyne; Rotich, Lucy; Chepkwony, Joel (elixirpublishers, 2017)
The paper sought to assess the effects of multimedia advertisement features on customer satisfaction in 5-star hotels in Kenya. The study was conducted in Nairobi which is the capital city of Kenya between the month of July and September, 2015. The city is endowed with top rated high-class hotels ranging from (1) to (5) star luxury hotels which are competing against each other. Classified hotels are trend setters in the tourism and hospitality industry. High classified hotels distinguish themselves by offering superior products and customized services. The mentioned reasons provided a good setup to conduct this research study. The research design for the study was explanatory research design. The target population comprised of the customers of the hotels listed. The total number of hotel rooms from which the sample was derived was 2500 rooms drawn from 15 five-star hotels. Purposive sampling was undertaken in order to distribute the sample size proportionately in accordance to the hotel room capacity. The customers were stratified and then systematic random sampling was used to select the samples who gave responses to the research instruments. The study established that multimedia online advertisement has significant effect on customer satisfaction by improving the interactivity and customer involvement with the brand it also enhances the presentation of the contents.
Keywords: Customer satisfaction; Multi-media; Advertisement features; 5-star hotels